Clinical applications of gamma delta T cells with multivalent immunity - Deniger, Drew C.; Moyes, Judy S.; Cooper, Laurence J. (Frontiers in Immunology, 2014)
Gamma delta T cells hold promise for adoptive immunotherapy because of their reactivity to bacteria, viruses, and tumors. However, these cells represent a small fraction (1-5%) of the peripheral T-cell pool and require activation and propagation to achieve clinical benefit. Aminobisphosphonates specifically expand the Vgamma9Vdelta2 subset of gamma delta T cells and have been used in clinical trials of cancer where objective responses were detected. The Vgamma9Vdelta2 TCR heterodimer binds multiple ligands and results in a multivalent attack by a monoclonal T cell population. Alternatively, populations of gamma delta T cells with oligoclonal or polyclonal TCR repertoire could be infused for broad-range specificity. However, this goal has been restricted by a lack of applicable expansion protocols for non-Vgamma9Vdelta2 cells. Recent advances using immobilized antigens, agonistic monoclonal antibodies (mAbs), tumor-derived artificial antigen presenting cells (aAPC), or combinations of activating mAbs and aAPC have been successful in expanding gamma delta T cells with oligoclonal or polyclonal TCR repertoires. Immobilized MHC Class-I chain-related A was a stimulus for gamma delta T cells expressing TCRdelta1 isotypes, and plate-bound activating antibodies have expanded Vdelta1 and Vdelta2 cells ex vivo. Clinically-sufficient quantities of TCRdelta1, TCRdelta2, and TCRdelta1negTCRdelta2neg have been produced following co-culture on aAPC, and these subsets displayed differences in memory phenotype and reactivity to tumors in vitro and in vivo. Gamma delta T cells are also amenable to genetic modification as evidenced by introduction of alpha beta TCRs, chimeric antigen receptors (CARs), and drug-resistance genes. This represents a promising future for the clinical application of oligoclonal or polyclonal gamma delta T cells in autologous and allogeneic settings that builds on current trials testing the safety and efficacy of Vgamma9Vdelta2 T cells.